Diversification of Labor Fishermen's Work in Meeting the Basic Needs of Families Post-COVID-19 in Kelantan Village, Langkat Regency - Mujahiddin Mujahiddin; Dhea Pulungan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article or paper aims to find a form of diversification of the work of labor fishermen groups in meeting the basic needs of exit after COVID-19 in Kelantan Village, Lalat Regency. The problem is focused on the impact of COVID-19 on the lives of fishermen in Kelantan Village, Langkat Regency, who are experiencing difficulties in meeting the basic needs of their families, so an adaptation strategy is needed to meet these needs, one of which is by diversifying work. To approach this problem, reference to adaptation strategies and the concept of job diversification, as well as the Precariat Theory of Guy Standing, is used. The data of this study were collected through in-depth observation and interviews with labor fishermen and then analyzed through the Miles and Huberman Interactive Model. This study concludes that diversification is an alternative livelihood choice by fishermen in the fisheries and non-fisheries sectors. The variety of jobs that fishermen can do highly depends on the resources available in their living environment. In Kelantan Village, labor fishermen diversify their work using boats as boat taxis. They work to meet the local transportation needs of remote coastal areas without road access. This service helps people deliver goods, school children, or transport tourists who want to explore the coast's natural beauty.